Study protocol for a controlled clinical trial on cardiac telerehabilitation and educational follow-up in patients with heart failure. - Jhonatan Betancourt-Peña; Iago Portela-Pino; María José Martínez-Patiño (PLoS ONE)
Background Heart failure is a primary non-communicable disease in Latin America and the Caribbean, which significantly reduces patients' quality of life. After diagnosis, emphasis is placed on cardiac rehabilitation and patient education regarding healthy lifestyles and habits. Interdisciplinary management is crucial in this process. However, lack of treatment adherence is a recurring issue in this population. In this context, technology allows us to address non-adherence to treatment. Its implementation helps overcome barriers and achieve treatment goals. Objective To determine the effects of a cardiac telerehabilitation-mediated exercise program and telephone educational follow-up on functional capacity in patients with heart failure, compared with cardiac telerehabilitation and conventional outpatient cardiac rehabilitation. Methods This article presents a SPIRIT-compliant protocol study of a three-arm, controlled, crossover clinical trial using participant blinding and simple sealed envelope block randomization. Conclusion According to the literature review, this can be considered the first three-arm clinical trial in the telerehabilitation of patients with heart failure. The measurement and intervention instruments are comparable and adequate compared to other studies. Trial registration ClinicalTrials.gov NCT05761639.